Skeletal muscle mass index predicts postoperative complications in intestinal surgery for Crohn's Disease - Galata, Christian; Hodapp, Janina; Weiß, Christel; Karampinis, Ioannis; Vassilev, Georgi; Reißfelder, Christoph; Otto, Mirko (Journal of parenteral and enteral nutrition, 2020)
Background - The aim of this study was to evaluate the role of the skeletal muscle mass index (SMI) for major postoperative morbidity in patients with Crohn's disease (CD) and intestinal surgery at a tertiary referral center.